Psych. The complete first season [videorecording (DVD)] - Roday, James; Hill, Dulé; Omundson, Timothy; Lawson, Maggie; Bernsen, Corbin, 1954-; Franks, Steve (Universal Studios Home Entertainment, 2011)
Thanks to a childhood spend with a family of cops, Shawn Spencer possesses an incredible photographic memory and notices seemingly insignificant details. These traits allow him to spend his jobless days providing the police with mystery-solving tips-- but his knowledge soon makes him a suspect. In order to clear his name, the unlikely sleuth declares that he has clairvoyant abilities and launches his own investigative agency, Psych. His skeptical best friend, Gus, is also on the case in this quirky television series.